Understanding Gen-Z Work Ethic and Leadership Management in the Digital Age - Rahmawati, Devie; Anindhita, Wiratri; Lumakto, Giri; Viendyasari, Mila; Wisesa, Rangga (Universitas Dharma Wacana, 2025)
This research examines serious challenges faced by the modernprofessional environment. The phenomena discussed include a lack ofwork ethics, limited appreciation for work, and insufficient professionalexperience among Gen Z workers, as well as leadership managementchallenges among Gen Y leaders. This study employs an ethnographicapproach, involving direct observation and participation at PT X andNGO Y to analyze these phenomena. The findings indicate that Gen Zworkers exhibit minimal work ethics and professionalism, lowappreciation for their jobs, and reduced motivation and commitment. Toaddress these challenges, this research recommends strengthening softskills education programs, developing detailed professionalismguidelines, enhancing administrative systems, and fostering an inclusivework culture. Implementing these recommendations is expected toincrease organizational productivity and create a harmonious multigenerationalworkplace. This research aims to contribute to a deeperunderstanding of multi-generational dynamics and offer practicalstrategies for effectively managing Gen Z talent